Alternative debt management strategies that can be employed by Lobels bread Bulawayo - Zhou, Rudo (Midalands State University, 2015)
Lobels Bread Bulawayo faces problem of rising debt, reduction in operational efficiency and increase credit sales due to mismanagement of debtors. This has motivated the researcher to evaluate the debt management strategies employed at Lobels Bread and how they can be harnessed to decrease bad debts. This study sought to look at the applicability of debt management strategies at Lobels, to identify risks associated with debt management and to determine factors affecting implementation of debt collection policies.Debt management strategies employed in bakeries included cash discounts, use of ageing analysis schedules, credit information evaluation. Alternatives strategies that could be used to do away with bad debtors included cutting supply, use of credit policies, taking legal action and monitoring payments. The risks affecting implementation of debt strategies included credit risk, inflation risk, taking bribes by employees and unintentional errors in recording or processing data. The researcher used descriptive research design in a population of 50 respondents and a census was conducted. Questionnaires and interviews were the main data collection techniques used to collect data and graphs and tables were used to present the data.The researcher concluded that the strategies currently implemented at Lobels Bread were not effective and the company was under staffed discouraging segregation of duties. The researcher therefore recommends that they improve on the timing of dispatching of invoices, enhance segregation of duties and lastly authorization approval of transactions to be done by appropriate personnel.